Starlight on Willow Lake - Wiggs, Susan (Don Mills, Ontario : Mira Books, 2015)
When caregiver Faith McCallum arrives at the enchanted lakeside estate of Avalon's renowned Bellamy family, she's intent on rebuilding her shattered life and giving her two daughters a chance at a better future. But she faces a formidable challenge in the form of her stubborn and difficult new employer, Alice Bellamy.
Keywords: Women caregivers -- Fiction; Rich people -- Fiction; Man-woman relationships -- Fiction; Interpersonal attraction -- Fiction; Family secrets -- Fiction; City and town life -- Fiction; Catskill Mountains (N.Y.) -- Fiction